“CARTE” (APLIKASI MOBILE PEMESANAN MENU RESTORAN PARTNER) - Kristin, Desi Maya; Rahardja, Giovan; Gui, Anderes (ISTEK WIDURI, 2022)
The Covid-19 pandemic changed how people work and interact, such as minimizing contact with others and things that others have touched. Especially when ordering from menus in restaurants. Many restaurants are converting their menu books to web-based individual restaurant menus. Due to the high quality of the photos, the need for a good internet connection and various web links makes ordering menus in restaurants difficult. The purpose of this study is to analyze the business process of ordering restaurant menus and designing restaurant menus in a mobile-based application. Qualitative research methods are used in this study. Interviews and direct observation are used as data collection methods. Analysis methods and object-based design (Object Oriented Analysis and Design) with UML (Unified Modeling Language) standardization. The research results are the design of use case diagrams, class diagrams, and user interfaces used by the customer as a user. Customers efficiently use a mobile app to order menus, which can be opened via a barcode scan that lists a table number or takeaway orders and pay cashless before ordering. With the mobile menu application, customer to servers or cashier interactions and customer-to-customer interactions are reduced as we do not have to struggle to open a restaurant website to order.